Fairness and Self-Interest in International Climate Protection - Lisandra Flach; Johannes Pfeiffer; Karen Pittel (Wirtschaftsdienst)
Abstract Fairness and self-interest shape international climate protection negotiations and measures, without always being clearly separable. The CO2 emissions included in international trade with Germany demonstrate which countries and regions could be particularly affected by EU protection measures based on self-interest. Fair burden-sharing between industrialised and developing countries is indispensable for global cooperation in climate protection. Only in this way can effective and economically efficient measures be implemented, which is in the interest of all states.